Arabidopsis pollen extensins LRX are required for cell wall integrity during pollen tube growth - Sede, Ana Rocío (2017)
Polarized growth of pollen tubes is an oscillatory mechanismwhich involves high trafficking of vesicles to the tip where aconstant remodeling of the cell wall occurs. To maintain the properassembly of the cell wall is crucial the role of glycoproteins and homogalacturonansin the crosslinking. Here, we studied the functionof four pollen specific LRX(8-11) (Leucine-Rich repeat Extensin-like)chimeric proteins which belong to the HRGP (Hydroproline-RichGlycoprotein) family in Arabidopsis thaliana. These LRX proteins have an LRR (Leucine rich repeat) N-terminal domain followedby a cysteine rich region and a C-terminal domain extensin (EXT)-likewith Ser-Pro repetitions. LRR domain might be involved inprotein-protein interactions and the role of EXT domain might be toestablish the crosslink on the cell wall allowing its integrity. Becausewe did not observe any obvious phenotype for the single mutantsand to overcome a possible functional redundancy, we obtainedmultiple homozygous loss of function mutants. The triple lrx9 lrx10lrx11 mutant displayed the most severe pollen tube phenotype withan important reduction (60.7%) in pollen germination and a lowerseed set (33% less compared to the WT). Moreover in vitro, semi invivo and in vivo analyses revealed the presence of abnormal pollentubes with widen tips and the emergence of bulges mostly near tothe tube tip. To study the composition of the primary cell wall in thetriple lrx9 lrx10 lrx11 mutant, we analyzed the distribution of pectins,callose and cellulose using different dyes. Confocal and bright-fieldfluorescence microscopy revealed an altered deposition of pectin,callose and cellulose and thicker cell walls in the triple mutant. Alltogether these results suggest that LRX8-11 have a structural roleand are required for a proper cell wall assembly during polarizedgrowth of pollen tubes.